Creation of Nanoparticle Carotenoid from Crude Palm Oil to Enhancing the Skin Color of Goldfish (Carassius auratus) - Pichitkul, Phongchate; Wongphonprateep, Siripong (Burapha Science Journal, 2026)
Production and trade of ornamental fish are profitable because of their aesthetic value. Fish that have particular colors and shapes are supplied to fulfill customer orders. Natural pigment is added to the skin color of ornamental fish by feed but reduction in ability of pigment absorption can cause color deterioration. Development of nanoparticle carotenoid from crude palm oil was studied to enhance goldfish skin color. Carotenoid nanoparticles were created by an ionotropic gelation process. A prepared solution containing carotenoids was freeze-dried and captured by a Scanning Electron Microscope (SEM). Mean particle diameter was determined as 131.56 ± 32.35 nm with Image J program and particle size and electrical potential of the surfaces were assessed using a Zetasizer, mean diameter was 177.567±14.00 nm with electrical potential of -30.233 ± 0.702 mV. NPC was incorporated into the feed at 0, 100, 200, 300, 400 and 500 µg kg-1 feed and fed to goldfish for 8 weeks. Measurement of goldfish color was performed by the CIE (L*, a*, b*) and (L*, c*, h*) system. The goldfish skin color intensity measured by CIE had shown that the fish fed with 500 µg kg-1 containing significantly highest skin color (p<0.05) without interfering on growth rate, survival rate and other side effect was not observed.